Hate and Perceived Threats on the Resettlement of Afghan Refugees in Portugal - João Prata Veiga; Luciana Oliveira (Societies, 2024)
The withdrawal of US troops from Afghanistan in August 2021 precipitated a humanitarian crisis, prompting the displacement of Afghan refugees seeking sanctuary, including in Portugal. This study aims to rigorously assess public perceptions of Afghan refugee resettlement in Portugal by analyzing national news and subsequent Facebook reactions, seeking to discern sentiment, approval/disapproval, perceived realistic and symbolic threats, and potential hate speech toward migrant resettlement. Employing a mixed-methods approach with a qualitative emphasis, this cross-sectional study involved a volumetric analysis of 40 Facebook posts from mainstream news outlets, followed by a qualitative content analysis of 1000 comments from 10 selected posts based on popularity and controversy. Findings reveal a predominance of negative sentiments and low levels of approval for migrant resettlement. Emotional complexity suggests controversy and polarization, with negativity surpassing positivity. Concerns regarding economic impact ranked highest, followed by security, cultural, and religious considerations. Instances of hate speech, predominantly political in nature, with lesser occurrences of religious and nationality-based content, were evident. This research contributes to the scientific understanding of public perceptions concerning Afghan refugee integration in Portugal, providing valuable insights into societal attitudes towards humanitarian crises and refugee resettlement efforts.